Problematics of Affirmative Action Policy Implementation of Women's Representation Quota in Surabaya City Election - Yuni Lestari; Gading Gamaputra; Firdausi Nuzula (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2021)
The development of an increasingly modern era is no longer a guarantee that a society's culture can be freedom from patriarchy as a whole. The women's equality has increasingly opened up opportunities for women to be active in both the domestic and public areas. The policy for affirming the quota for women's representation was also formulated by following developments. The 30% quota policy for women's representation in political parties is one of the affirmative policies in realizing women's equality in politics in Indonesia. By using descriptive quantitative research methods, this study tries to describe how the implementation of the affirmation policy on the quota of women's representation can work. The results that can be obtained in this study include: (1) in every election process, both the registration process for prospective DPRD members, the process of establishing a temporary candidate list (DCS) and the process of determining the permanent candidate list (DCT) as a whole has complied with quota of 30% women's representation (2) However, it cannot be denied that at every stage of implementation of the policy, there are still many problems